The Benefit of YouTube Videos as a Source of Information on Tinnitus for Patients - Bakshi, Satvinder Singh; Kalidoss, Vinoth Kumar; Ramesh, Seepana; Das, Soumyajit (International Archives of Otorhinolaryngology, 2023)
Introduction Tinnitus is one of the most common otological complaints encountered. Patients often use the internet, especially YouTube videos, as a source of information regarding their health condition. There is a need to analyze the standard and quality of information in these videos so that the patients receive correct information.Objective The purpose of the present study was to evaluate the reliability and utility of YouTube videos on tinnitus.Methods The first 100 videos on YouTube using the search terms tinnitus and ringing in the ear were identified. Three subject experts assessed the reliability using the modified five-point DISCERN score and utility using a usefulness score. Various indices like view ratio, like ratio, video power index, and interaction index were also calculated.Results Out of the 100 videos selected, 34 were excluded; collectively the remaining 66 videos were viewed 12,797,730 times. The most common upload sources were hospital/physician (39%), paramedic health care providers (19%), and alternative medicine (19%). The discern score was the highest in hospital/physician group (mean 19.3) and lowest in patient experience group (mean 13.4). A negative correlation was observed between the number of views (correlation coefficient −0.214), number of likes (correlation coefficient −0.242), number of comments (correlation coefficient −0.242), and the usefulness score.Conclusion Although there are multiple videos on YouTube regarding tinnitus, the overall educational content and reliability of the videos are poor. Video popularity is not associated with usefulness. Healthcare providers should counsel patients regarding videos on YouTube and try to create more comprehensive videos.
Keywords: tinnitus; health Education; social media; complimentary therapies